Redescription of Manayunkia caspica Annenkova, 1929 and M. danubialis Băcescu, 1944 n. comb. (Fabriciidae, Sabellida, Polychaeta) - Bick, Andreas; Oberrisser, Philipp; Bastrop, Ralf (Zootaxa, 2024)
The spread of the subspecies M. caspica danubialis Băcescu, 1944, which has been found in the Danube since 1944, into the upper section of the Danube as far as Austria was the reason for describing the characters of this species and comparing it with the nominotypical subspecies M. caspica caspica Annenkova, 1929, which lives in the Caspian Sea. Both subspecies are similar in the most important diagnostic characters, such as the number of branches of the radioles and the presence and number of pseudospatulate chaetae on thoracic chaetigers. However, they differ in other, less conspicuous characters, such as the number of thoracic uncini and the length of chaetigers. But these characters vary depending on the size of the specimens. Both subspecies inhabit completely different habitats. Based on the ecological species concept, the spatially and ecologically separated populations are regarded as distinct species, M. caspica, and M. danubialis n. comb. The occurrence of transitional uncini in both species and the presence of a brood chamber in the females of M. caspica are described for the first time. The structure of the radiolar crown is also described for both species. A molecular barcode for M. danubialis n. comb., a 654 base pair fragment of cytochrome c oxidase I is presented, allowing a fast and simple identification of this species by using a robust PCR/sequencing approach.